TEKNOLOGI PEMBUATAN ALAT DAN PERHIASAN DI GUA KIDANG, BLORA - Nurani, Indah Asikin (BRIN, 2016)
Gua Kidang is a prehistoric settlement that provides a complete description on the lifeÂ pattern and the development of technology, as well as the adaptation strategy of the dwellers toÂ survive. The development of technology was supported by the intelligence of the artist and the rawÂ material provided in its neighbourhood. The manufacturing technique of tools and jewellery,Â found in Gua Kidang, demonstrated the effectivity aspect and unique innovation. Artifacts madeÂ from clamshell and bone, along with dental remains provide the insight on the variety of tools typeÂ and advance manufacturing technique compared to the type found in other prehistoric caveÂ dwelling in Java as well asIndonesial. Based on the analysis of the manufacturing technique andÂ geoarchaeological aspect, the cultural character of Gua Kidangâ€™s dwellers was shown through theÂ development of technology. This paper uses descriptive methods - explanatory with inductiveÂ reasoning.